2019
DOI: 10.1002/anie.201912668
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of Methane Transformation over Copper‐Exchanged Mordenite as Revealed by In Situ NMR and IR Spectroscopy

Abstract: The reaction of methane with copper‐exchanged mordenite with two different Si/Al ratios was studied by means of in situ NMR and infrared spectroscopies. The detection of NMR signals was shown to be possible with high sensitivity and resolution, despite the presence of a considerable number of paramagnetic CuII species. Several types of surface‐bonded compounds were found after reaction, namely molecular methanol, methoxy species, dimethyl ether, mono‐ and bidentate formates, CuI monocarbonyl as well as carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
70
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 72 publications
11
70
1
Order By: Relevance
“…These extra‐framework oxygen and carbon atoms probably constitute the adsorbed methane conversion intermediate, the methoxy [Cu 1+ ‐OCH 3 ] species. This intermediate species has previously been observed by C 13 CP/MAS NMR in low‐aluminum content mordenite, [30] which also contains paired monomer active sites. These methoxy species goes on to form methanol in the extraction step and corroborates the hypothesis that the reaction is taking place between the coppers on either side of the narrow 8‐ring channel where methane has to diffuse through the convoluted 3‐dimensional 8‐ring channel system to reach the active sites.…”
Section: Figuresupporting
confidence: 67%
“…These extra‐framework oxygen and carbon atoms probably constitute the adsorbed methane conversion intermediate, the methoxy [Cu 1+ ‐OCH 3 ] species. This intermediate species has previously been observed by C 13 CP/MAS NMR in low‐aluminum content mordenite, [30] which also contains paired monomer active sites. These methoxy species goes on to form methanol in the extraction step and corroborates the hypothesis that the reaction is taking place between the coppers on either side of the narrow 8‐ring channel where methane has to diffuse through the convoluted 3‐dimensional 8‐ring channel system to reach the active sites.…”
Section: Figuresupporting
confidence: 67%
“…At this point we note that two recent publications 165,166 have shown that nuclear magnetic resonance ( 1 H, 13 C, 27 Al, 29 Si) studies also have a significant potential for contributing to the understanding of this conversion. These studies have shed considerable light as to the range of products that result from reaction of activated Cu II with methane, and where they may end up within the zeolite structure.…”
Section: Summary Of Evidence Regarding Reaction Mechanisms and The Namentioning
confidence: 84%
“…formaldehyde and the presence of both mono-and bi-dentate formates. 165 Herein, however, we shall concentrate on those methods that have: firstly, the capacity to restore information that directly concerns the nature of the copper sites present and how they behave; secondly, that have a clear and present potential to be applied in an operando manner; but that, thirdly, as of yet, have not been applied to the selective conversion of methane to methanol using copper-containing zeolites.…”
Section: Summary Of Evidence Regarding Reaction Mechanisms and The Namentioning
confidence: 99%
“…Next, we have shown two important applications of this finding by computing the IR spectra of two test cases: (i) Ni 4 O 6 (CH 4 ) 2 and (ii) Ni 4 O 7 (CH 4 ) 2 . IR spectroscopy covers the infrared region of the electromagnetic spectrum with frequencies ranging from 4000 cm −1 to 40 cm −1 [74][75][76][77][78] . In IR spectroscopy, specific frequencies are absorbed by the molecules that are the characteristic of their structure.…”
Section: Comparing the Role F Vib In ∆G(t P): Importance Of Capturinmentioning
confidence: 99%